2020
DOI: 10.1002/arcp.1067
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive experiences as information: Processing fluency in consumer judgment and decision making

Abstract: Thinking is accompanied by metacognitive experiences of ease or difficulty. People draw on these experiences as a source of information that can complement or challenge the implications of declarative information. We conceptualize the operation of metacognitive experiences within the framework of feelings‐as‐information theory and review their implications for judgments relevant to consumer behavior, including popularity, trust, risk, truth, and beauty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 227 publications
(289 reference statements)
3
59
0
Order By: Relevance
“…An important quality of preconscious influences is that they are trusted as valid signals or cues about external reality. Coming into our minds so effortlessly and without any cognitive work on our part, they are experienced as “out there” in the world instead of the result of any inference or assumption on our part and so tend to be trusted as accurate and valid in the same way we trust other incoming sensory information (Jones & Nisbett, 1971; Schwarz et al, 2021). This subjective validity gives preconscious inputs considerable power in subsequent conscious decisions and behavior.…”
Section: Preconscious Inputs Into Conscious Choice Processesmentioning
confidence: 99%
“…An important quality of preconscious influences is that they are trusted as valid signals or cues about external reality. Coming into our minds so effortlessly and without any cognitive work on our part, they are experienced as “out there” in the world instead of the result of any inference or assumption on our part and so tend to be trusted as accurate and valid in the same way we trust other incoming sensory information (Jones & Nisbett, 1971; Schwarz et al, 2021). This subjective validity gives preconscious inputs considerable power in subsequent conscious decisions and behavior.…”
Section: Preconscious Inputs Into Conscious Choice Processesmentioning
confidence: 99%
“…Furthermore, future studies could address one aspect of language processing that was not directly addressed in the current research, namely fluency. Numerous studies have shown how fluency, that is the ease with which a text can be processed, enhances its liking (Reber et al, 2004), perceived truthfulness (Dechêne et al, 2009), and its trustworthiness (Newman et al, 2014; for an overview, see Schwarz et al, 2020). When research was presented with high audio quality or easy-to-read fonts, thus in a way that could be processed easily instead of hard, it was perceived to be of higher quality and the associated researchers were perceived to be more competent and intelligent (Newman & Schwarz, 2018; Oppenheimer, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Coelho et al, 2020) and sensory marketing research (e.g. Elder & Krishna, 2021;Schwarz et al, 2021). Broadly speaking, these domains represent three core theoretical perspectives to view the various aspects of SBE-namely, the ecological perspective (e.g.…”
Section: Overview Of Sensory Brand Experiencementioning
confidence: 99%